A Fully Immersive Set-Up for Remote Interaction and Neurorehabilitation Based on Virtual Body Ownership - Perez-Marcos, Daniel; Solazzi, Massimiliano; Steptoe, Will; Oyekoya, Wole; Frisoli, Antonio; Weyrich, Tim; Steed, Anthony; Tecchia, Franco; Slater, Mel; Sanchez-Vives, Maria V. (Frontiers in Neurology, 2012)
Although telerehabilitation systems represent one of the most technologically appealing clinical solutions for the immediate future, they still present limitations that prevent their standardisation. Here we propose an integrated approach that includes three key and novel factors: (a) fully immersive virtual environments, including virtual body representation and ownership; (b) multimodal interaction with remote people and virtual objects including haptic interaction; and (c) a physical representation of the patient at the hospital through embodiment agents (e.g., as a physical robot). The importance of secure and rapid communication between the nodes is also stressed and an example implemented solution is described. Finally, we discuss the proposed approach with reference to the existing literature and systems.